Risk factors for hamstring injuries in male soccer players: A systematic review of prospective studies - van Beijsterveldt, A. M.; van de Port, I. G. L.; Vereijken, A. J.; Backx, F. J. G. (Scandinavian Journal of Medicine & Science in Sports, 2013)
Hamstring injuries are common injuries in soccer players. In view of the high incidence and the serious consequences, identifying risk factors related to hamstring injuries is essential. The aim of this systematic review was therefore to identify risk factors for hamstring injuries in male adult soccer players. PubMed, Embase/Medline, Cumulative Index to Nursing and Allied Health Literature, and SPORTDiscus were systematically searched, and prospective studies investigating risk factors for hamstring injuries in adult male soccer players were included. The methodological quality of the included articles was assessed using a standardized set of predefined criteria. Seven of the 11 studies identified, involving a total of 1775 players and 344 hamstring injuries, met the inclusion criteria. All but one of the included studies met at least five of nine methodological criteria, causing them to be qualified as `high quality`. The included studies used univariate as well as multivariate analyses to identify risk factors for hamstring injury. The results from the multivariate analyses suggest that previous hamstring injury is most strongly related to hamstring injury. Conflicting evidence is found for age and hamstring length or flexibility as risk factors for the occurrence of hamstring injuries.